P63 Ribavirin uptake by primary human hepatocytes corresponds to equilibrative nucleoside transporter 1 expression. (6th September 2011) - Baloch, B K; Chen, L; Ilyas, M; Irving, W; Thomson, B J
Abstract : Introduction: Combined therapy with pegylated interferon (INF) and ribavirin (RV) is the current standard of care for HCV infection, with a 40% to 80% success rate depending on viral genotype. The achievable concentration of RV is an important determinant of therapeutic outcome. A preliminary study used cryopreserved hepatocytes ( J Hepatology 2010;52 :469–71) to show that equilibrative nucleoside transporter 1 (ENT1) is a major RV transporter. In this study we confirm this observation and demonstrate that the level of ENT1 expression is variable and strongly and directly correlated with RV uptake in primary human hepatocytes. We also provide evidence that ENT1 expression alone may not be sufficient for RV uptake and observe that its levels are not influenced by interferon α. Aim: The aim of this study was to assess RV uptake levels and compare it with ENT1 expression in freshly isolated primary hepatocytes. We also aimed to see effects of interferon α on ENT1 expression and ribavirin uptake. Method: Primary hepatocytes were isolated from liver tissue obtained from six human donors. Hepatocytes were cultured on collagen coated plates and exposed to RV diluted in culture medium. Parallel samples were taken for High Performance Liquid Chromatography to assess RV uptake and for quantitative PCR to evaluate ENT1 expression. Similar assays were performed on human hepatoma cell line (Huh7). ENT1 (SLC29A1) gene sequence was analysed by cloning of PCR amplified cDNA followed by direct sequencing. Results: We have studied six human livers. As illustrated in Abstract P63 figure 1, there was a strong direct correlation between levels of expression of ENT1 and RV uptake at 24 h (rs =0.94; p value =0.01). Addition of interferon did not influence RV uptake or ENT1 expression. Strikingly, Huh7 cells expressed ENT1 at similar levels to the majority of primary hepatocytes, but did not take up RV. Sequencing data revealed that ENT1 in Huh7 is wild type. Conclusion: ENT1 has been previously identified as a major transporter involved in RV uptake. In this study, we clearly demonstrate that RV uptake in different sets of primary human hepatocytes is variable and correlates with ENT1 expression. This variation in ENT1 expression may account for differences in response rate in patients receiving anti-HCV therapy. Interferon modulation of ENT1 seems to be a highly unlikely mode of RV and interferon synergistic action in HCV infection. Outcomes in the Huh 7 cell line suggest that, while ENT1 may be necessary, other factors are required to mediate RV uptake.